INTEGRATED AGRICULTURE-BASED AGROTOURISM MODEL WITH ECO-FRIENDLY ENVIRONMENTALISM ON CARIK INJEMAN LAND IN CIBODAS VILLAGE - Indrawati, Etty; Ruchiat, Ratnaningsih; Indrawati, Dwi; Febriyani, Shafira (Journal of Environmental Science and Sustainable Development, 2020)
An integrated agriculture-based agrotourism model needs to be implemented in the Carik Injeman area of Cibodas village. To date, Carik Land, with an area of 30 hectares to date, has not been optimally used. Cibodas villagers mostly work as farmers and ranchers. More than 50% of the workforce does not have permanent employment. Some previous researchers have said that with integrated agriculture, independent communities could increase their land resources and farmers would prosper in a sustainable manner. The aim of this study was (1) to identify the factors that determine agrotourism planning in Carik land, (2) study integrated farming systems as support for agrotourism, (3) inventory the various opinions of village groups and community leaders related to agrotourism development (4) formulate an agrotourism model in integrated agriculture. This research uses descriptive, qualitative, observational, and quantitative methods, in particular Likert scales. Data collection uses questionnaires through purposive sampling. The results show that the community response supported by the FGD results on agrotourism planning was very good. SWOT analysis was made to study the agrotourism planning factor. The sustainable agrotourism plan to be located on Carik Injeman’s land must have four zones, namely an: 1) integrated farming system area, 2) integrated waste disposal area, 3) environmental area, 4) and recreation and sports area. The study results can be used as a recommendation for agrotourism planning in Carik Injeman land, Cibodas village, Bandung.